캐나다 부부재산제도와 혼인주택(matrimonial home) - 우리나라 부부재산법제에 주는 몇 가지 시사점 - 이연이(Yeon-I, Lee); 김제완(Je-Wan, Kim) (이화젠더법학, 2021)
현행 부부별산제에서는 재산명의자가 배우자 동의 없이 재산을 처분하는 것이 가능하나, 혼인 중 협력하여 이룩한 실질적 공유재산의 일방적 처분은 명의를 가지지 않은 배우자의 지분권을 침해하는 것으로 부당하다. 경제적 공동체라는 부부의 특성상 혼인재산은 그 명의와 기여도가 반드시 일치하지 않는다, 그러나 명의자가 처분권을 가지므로 부부 중 누가 재산 명의를 가지는지가 부부간 경제적 지위와 균형에 직접적인 영향을 미친다. 특히, 부부가 공동으로 거주하는 주택은 가족생활의 기초가 되는 주택으로서 대부분 가정의 중요한 자산에 해당한다는 점에서 특별한 보호가 필요하다. 캐나다는 가족법상 혼인주택(matrimonial home)의 처분에 배우자 동의가 필요하도록 일정한 제한을 두어 부부재산의 일실을 방지하고 있다. 반면, 우리 법제에서는 민법 제839조 3의재산분할청구권 보전을 위한 사해행위취소권을 규정하고 있다. 그러나 부부간 실질적 형평을 위해서는 이혼시 균등한 재산분할이 되도록 할 뿐만 아니라, 혼인 중에도 재산명의자가 부부공동재산을 일방적으로 처분하지 못하도록 할 필요가 있다. 이를 위해서는 별산제하에서의 재산처분의 자유와 혼인관계의 특수성에서 오는 가족법적 제한을 조화하는 방안이 모색 되어야 할 것인데, 캐나다 혼인주택 제도에서 나타나는 부부공동재산 법리는 우리 부부재산법제에 여러가지 시사하는 점이 있으며 재산분할청구권 보전을 위한 사해행위 취소권의 운용에도 일응 기준을 제시할 수 있을 것이다. The matrimonial property that a couple has achieved in bilateral cooperation as an economic community during the marriage has the substance of shared property, at least between couples. Under a separate property regime, it is not a problem in terms of property law for a spouse with the title to dispose of a property without the spousal consent, but if the owner unilaterally disposes of matrimonial property, it is against marital equity. In particular, it is unjust to unilaterally dispose of a matrimonial home, regardless of which spouse holds the title, given that the home is occupied as a family residence in their course of regular family life and is the largest asset for most families. Canada’s matrimonial home is a system under family law. If a title-holding spouse wants to sell, mortgage, otherwise dispose of an interest in the matrimonial home, the other spouse’s consent is required. In comparison, The Korean Civil Act has established the legal basis for revoking the spouse’s unilateral disposition by recognizing the Right to Revoke Fraudulent Act for Preservation of Claim for Division of Property in Article 839-3. The right to revoke the spouse’s unilateral disposition to preserve the right to claim property division is not just for equalizing property division at the time of divorce. To operate the system effectively, unilateral disposition without spousal consent should be set aside and restored to its original state, even if the divorce is not gotten. Suppose we refer to the matrimonial home rules and limit the subject to unilateral dissipation is restricted, that could harmonize rights and obligations arising from the peculiarity of the marital relationship with the freedom of property disposition under property law. KCI Citation Count: 0